Experimental study for polarimetric measurement of RFID transfer function with in an indoor environment - Duangsuwan, S.; Leukachorn, T.; Chinsawatpan, S.; Promwong, S. (My University, 2009)
Radio Frequency Identification (RFID), is unlicensed industrial, scientific, and medical (ISM) band at 2.4 GHz. The same principle as that used in long-range radio communication links. The reader's antenna generates a propagating radio wave use far-field communication, which is received by the antenna in the tag. This paper, the microstrip patch antennas used both for transmitter antenna and receiver antenna likewise the reader antenna and tag antenna, simple patch antenna of this type radiates a linearly polarized wave. We investigated the transmission loss the RFID short range systems. Furthermore, we believed our studies can be designed the antennas for RFID systems. ©2009 IEEE.
Keywords: Channel transfer function; Friis' transmission formula; Polarimetric measurement; RFID transmission loss